2015
DOI: 10.1523/jneurosci.3542-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Gene Dosage in the Dysbindin Schizophrenia Susceptibility Network Differentially Affect Synaptic Function and Plasticity

Abstract: Neurodevelopmental disorders arise from single or multiple gene defects. However, the way multiple loci interact to modify phenotypic outcomes remains poorly understood. Here, we studied phenotypes associated with mutations in the schizophrenia susceptibility gene dysbindin (dysb), in isolation or in combination with null alleles in the dysb network component Blos1. In humans, the Blos1 ortholog Bloc1s1 encodes a polypeptide that assembles, with dysbindin, into the octameric BLOC-1 complex. We biochemically co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 84 publications
1
49
1
Order By: Relevance
“…In addition, BLOS2 may have a function in the nucleus (Sun et al, 2008). Second, the residual activity of the destabilized subunit outside of BLOC-1 may function in some way that is different from a null mutation itself, suggesting that phenotypes are differentially sensitive to genetic dosages of loss-of-function BLOC-1 alleles (Mullin et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…In addition, BLOS2 may have a function in the nucleus (Sun et al, 2008). Second, the residual activity of the destabilized subunit outside of BLOC-1 may function in some way that is different from a null mutation itself, suggesting that phenotypes are differentially sensitive to genetic dosages of loss-of-function BLOC-1 alleles (Mullin et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…In mammals and flies, Dysb associates with seven other proteins to form BLOC-1 (biogenesis of lysosome-related organelles), a complex implicated in several aspects of membrane trafficking and fusion (Mullin et al 2011. Genetic interaction experiments support the idea that the BLOC-1 components Snapin and Blos-1 cooperate with Dysb to mediate homeostatic plasticity in Drosophila (Dickman et al 2012;Mullin et al 2015), and like Dysb, Snapin localizes to SVs (Dickman et al 2012). The mechanism of how Dysb and its interactors function in homeostatic compensation is unclear, but might involve regulation of SNARE-mediated fusion events, as BLOC-1 components have been shown to interact with SNAREs and NSF (Ghiani et al 2010;Gokhale et al 2015), and overexpression of NSF rescues the ability to respond to PhTx in dysb mutants (Gokhale et al 2015).…”
Section: Homeostatic Plasticitymentioning
confidence: 90%
“…The authors report improvement of cognitive functions and memory by using the sphingolipid Fingolimod in a well‐studied mouse model lacking the dysbindin‐containing complex Biogenesis of lysosome‐organelle complex‐1 (BLOC‐1). Dysbindin was associated with schizophrenia (Straub et al, ) and later found to be part of BLOC‐1 in tissues such as liver (Li et al, ) and brain (Ghiani et al, ), as well as in invertebrates (Mullin et al, ). Even though the genetic association between dysbindin and schizophrenia has not been proven strong (Straub et al, ; Farrell et al, ), several reports have pointed out that this complex may play a role in brain function and, most importantly, including its development (Ryder and Faundez, ; Ghiani and Dell' Angelica ; Mullin et al, ).…”
mentioning
confidence: 99%